Jean Watson’s Theory of Human Caring and its Applicability in Nursing Care and Education: An Integrative Review - da Rocha Afonso, Shirley (2025)
Introduction: It is important to identify the current scenario of transpersonal nursing care and how the training scenarios of the Theory of Human Care are constructed according to the precepts of Jean Watson. Objective: To integrate and analyze the application of Jean Watson’s Theory of Human Caring in nursing studies, particularly in terms of care provision and educational practices within the nursing field. Method: Integrative Review based on Whittemore and Knafl. The search strategy encompassed the following databases: Web of Science, PubMed/Medline, Embase, Scielo, Lilacs, Scopus, and Cinahl, with no time restrictions. A thematic analysis was performed to synthesize the findings of the review and relevant information from the selected articles was extracted. The PRISMA checklist and quality appraisal were used to ensure the robustness of the identified publications. Results: Thirty-two articles met the eligibility criteria and were included in this review. Three themes emerged: 1. Unveiling the dimensions of care in the light of Jean Watson’s ideas; 2. Beyond the concept of care; 3. Care management and organizational culture. The significance of adopting transpersonal care approaches in caring for individuals with illness is highlighted, facilitating moments of spiritual and safe care. Nurses are required to possess both knowledge and skills to enable the provision of more meaningful care, alongside integrating material, educational, and human resources to enhance this caregiving process. Conclusion: The findings emphasize the importance of cultivating specialized skills within nursing practice, highlighting the necessity of specialized training and education focused on transpersonal care principles.